Induction of Listeria monocytogenes infection by the consumption of ponderosa pine needles. - Adams, C J (1979)
An infectious microorganism, identified as Listeria monocytogenes, has been isolated from the bloodstream of pregnant mice fed a diet containing Pinus ponderosa needles. When the isolate was injected into pregnant mice, reproductive dysfunction and other changes, including speckled livers, spleen atrophy, and hemorrhagic intestines, appeared to mimic the signs of the disease in pregnant mice fed pine needles. Moreover, these pathological changes are similar to those observed in cattle and other mammals experiencing abortions or toxemia, or both, attributed to the ingestion of P. ponderosa needles, suggesting that L. monocytogenes may be a part of the etiology of "pine needle abortion."